Power Doppler sonography and ultrasound contrast agent in assessing rheumatoid synovitis - M. Carotti; E. Filippucci; F. Salaffi (PAGEPress Publications, 2002)
Pannus formation is a fundamental event in the pathogenesis of rheumatoid arthritis and its hypervascularisation seems to be crucial to the development of joint damage. High-resolution greyscale ultrasonography is a safe, quick, and inexpensive imaging tool that allows an accurate detection of even minimal morphostructural changes in patients with rheumatoid arthritis, including joint effusion, thickening of synovial membrane and bone erosions. More recently, power Doppler sonography has proved to be a reliable tool for semiquantitative assessment of the vascularity of the synovial tissue. The contrast-enhanced power Doppler sonography seems to be a helpful adjunct in assessing synovitis and the therapeutic response to the different therapies in patients with rheumatoid arthritis. The aim of this radiological vignette was to show a representative example of use of power Doppler sonography with contrast agent in assessing rheumatoid synovitis.